Laboratory studies of heated Bulk Fill composite in the tooth cavity during filling of teeth with carious defects - V. A. Kriventseva; Y. B. Vorobieva; V. V. Nikitenko (Эндодонтия Today)
Aim. To study with the help of a microscope the marginal fit of Bulk-Fill group composite materials to the hard tissues of the tooth. Optimize the method of heating the composite in the cavity.Materials and methods. The marginal fit of the composite material of the Bulk-Fill group, sealed in 30 teeth of chewing anatomical and functional accessories extracted according to various indications, was studied. Materials used in the laboratory experiment: 3M ESPE Filtek posterior restorative Bulk Fill, SDR (Dentsply Sirona), Sonic Fill (Kerr). According to the manufacturers, the materials are used with the method of single-portion sealing. The research was conducted at the Department of General Dentistry of the S.M.Kirov Military Medical Academy of the Ministry of Defense of the Russian Federation.Results. 30 teeth extracted according to various indications of chewing anatomical and functional accessories were indicators were shown by the Sonic Fill (Kerr) system, due to heating and changing the viscosity of the material.Conclusions. It was proved in the laboratory that the heated composites of the Bulk-Fill group had the best edge fit during sealing than composites at normal room temperature. A nozzle was developed for heating the composite in the tooth cavity (priority application No. 2021120658 dated 12.07.2021).